Identification of Sexual Dimorphism in Nyctixalus margaritifer Based on Morphometric Analysis at Situ Gunung Sukabumi - Wahyu Prihatini; Rouland Ibnudarda; Mutia Anggraeni; Boby Darmawan (Jurnal Biodjati, 2025)
The Nyctixalus margaritifer frogs is a native species on Java island, and nature's existence is increasingly threatened. This species has very limited distribution in West Java, and there is no information regarding sexual dimorphism. Therefore, this research aimed to explore the presence of N. margarite in the Situ Gunung area in the Gunung Gede Pangrango National Park (TNGGP) and analyze sexual dimorphism based on morphometrics. The research was conducted in September-December 2023, and data were collected using the Visual Encounter Survey (VES) method. The coordinates of individual N. margaritifer were recorded using GPSMAP, followed by analyzing 23 morphometric characters using the non-parametric Mann-Whitney. The Principal Component Analysis (PCA) was carried out to determine characters that form group structures. The data obtained were tested using the Bartlett homogeneity variance test and declared significant at p-value <0.05. The statistical analysis was performed using R software. The results showed that there were 6 males and 10 females of N. margaritifer in 4.34-hectare home range found at 10-80 cm height from the ground, attached to the leaves or stems of fern Shillaginella sp., taro Homalomena sp., Cyrtandra sp., and Laportea sp. Regarding defensive behavior in the presence of humans, N. margaritifer were observed to stop moving and making sounds, pressed their limbs on the perches, remained still, and appeared dead. The results of the analysis obtained three characters that differentiate sex with significant p-value <0.05, namely snout-vent length (SVL), third toe length (T3), and wrist width (Lt.M). PCA scatter plot showed that the three characters did not contribute maximally as separators. Meanwhile, the K mean cluster analysis produced clustering of SVL, T3, and Lt.M, which was not strong enough to be used as sex-distinguishing characters.